2005
DOI: 10.1196/annals.1313.004
|View full text |Cite
|
Sign up to set email alerts
|

BAFF Overexpression Is Associated with Autoantibody Production in Autoimmune Diseases

Abstract: The B-cell activity factor (BAFF) acts as a positive regulator of B-cell function. To gain further insight into the understanding of B-cell hyperactivity in autoimmune diseases, the serum level of BAFF was determined in 43 systemic lupus erythematosus (SLE) patients, 58 primary Sjögren's syndrome (pSS) patients, 28 rheumatoid arthritis (RA) patients, and 68 normal control subjects using an in-house sandwich ELISA. A commercial kit was used to detect soluble CD23 (sCD23) reflecting B-cell activation. In-house a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
192
4
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 312 publications
(218 citation statements)
references
References 17 publications
11
192
4
11
Order By: Relevance
“…BAFF overexpression, observed in serum, saliva, and MSGs of pSS patients, particularly those with GCs, rescues auto-reactive cells from depletion in the periphery, leading to higher number of mature auto-reactive B cells [24,[37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…BAFF overexpression, observed in serum, saliva, and MSGs of pSS patients, particularly those with GCs, rescues auto-reactive cells from depletion in the periphery, leading to higher number of mature auto-reactive B cells [24,[37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Several cross-sectional studies showed that approximately 30% of SLE patients had significantly elevated circulating levels of BAFF/BLys [Cheema et al 2001;Zhang et al 2001]. Elevated BAFF/BLys levels appeared to correlate with increased total IgG and autoantibody (particularly anti-dsDNA) levels [Cheema et al 2001;Pers et al 2005], and, in some studies, with increased disease activity (as measured by SLEDAI) [Becker-Merok et al 2006]. A recent study has shown that excessive productions of IFNγ by activated T cells may be responsible for the induction of BAFF/BLyS production by monocytes and macrophages in lupus patients [Harigai et al 2008].…”
Section: Type I Ifns and Ifn-inducible Genes And Chemokinesmentioning
confidence: 99%
“…Elevated levels of BAFF have been detected in serum and synovial fluid samples from patients with rheumatoid arthritis (RA), and it was recently demonstrated that overproduction of BAFF by dendritic cells and macrophages may play a crucial role in the pathogenesis of experimental arthritis (8,9).…”
mentioning
confidence: 99%